Public sector accounting policy reform in the Czech Republic: Experience from local governments (pilot) - Filip Hrůza; Petr Valouch (European Financial and Accounting Journal, 2016)
The Czech Republic has recently introduced and implemented public sector accounting reform. The aim of the reform was to make the Czech public finance system more transparent, efficient and realistic. The authors of this reform, in fact, intended to bring public sector accounting and public financial management closer to private sector practices that, from their point of view, fulfil the reform goals previously mentioned. After a few years of functioning in this new accounting environment, certain associated points and problems have arisen that have to be tackled. The aim of this paper is to describe public sector accounting reform and its post-implementation process to current state in the Czech Republic based on pilot empirical research mirroring the opinions and experience of municipal Chief Financial Officers and its comparison with similar examples from other countries. The pilot sample for this research consists of municipal Chief Financial Officers and the research method is based on questionnaires and interviews with them. Results and findings achieved by this pilot research show that the reform of the new public sector accounting system in the Czech Republic has been developed in very extended scope in comparison with other countries, estimated costs perceived by users (local governments) are prevailing over advantages and benefits and thus there was identified certain degree of scepticism which may disrupt further efficient and positive use of this new accounting system.
Keywords: M41; M48; 650; Accounting; Financial management; Municipal; Public sector; Reform